Engineered Lactococcus lactis Secreting IL-23 Receptor-Targeted REX Protein Blockers for Modulation of IL-23/Th17-Mediated Inflammation - Plavec, Tina Vida; Kuchař, Milan; Benko, Anja; Lišková, Veronika; Černý, Jiří; Berlec, Aleš; Malý, Petr (Microorganisms, 2019)
Lactococcus lactis, a probiotic bacterium of food origin, has recently been demonstrated as a suitable strain for the production and in vivo delivery of therapeutically important proteins into the gut. We aimed to engineer recombinant L. lactis cells producing/secreting REX binding proteins that have been described as IL-23 receptor (IL-23R) blockers and IL-23R antagonists suppressing the secretion of cytokine IL-17A, a pivotal step in the T-helper Th17-mediated pro-inflammatory cascade, as well as in the development of autoimmune diseases, including inflammatory bowel disease (IBD). To reach this goal, we introduced cDNA sequences coding for REX009, REX115, and REX125 proteins into plasmid vectors carrying a Usp45 secretion signal, a FLAG tag sequence consensus, and a LysM-containing cA surface anchor (AcmA), thus allowing cell-surface peptidoglycan anchoring. These plasmids, or their non-FLAG/non-AcmA versions, were introduced into L. lactis host cells, thus generating unique recombinant L. lactis-REX strains. We demonstrate that all three REX proteins are expressed in L. lactis cells and are efficiently displayed on the bacterial surface, as tested by flow cytometry using an anti-FLAG antibody conjugate. Upon 10-fold concentration of the conditioned media, a REX125 secretory variant can be detected by Western blotting. To confirm that the FLAG/non-FLAG REX proteins displayed by L. lactis retain their binding specificity, cell-surface interactions of REX proteins with an IL-23R-IgG chimera were demonstrated by flow cytometry. In addition, statistically significant binding of secreted REX009 and REX115 proteins to bacterially produced, soluble human IL-23R was confirmed by ELISA. We conclude that REX-secreting L. lactis strains were engineered that might serve as IL-23/IL-23R blockers in an experimentally induced mouse model of colitis.